2020
DOI: 10.1002/ange.202008518
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic versus Thermodynamic Control Over Multiple Conformations of Di‐2,7‐naphthihexaphyrin(1.1.1.1.1.1)

Abstract: rating two built-in 2,7-naphthylene moieties was synthesized as two separate,c onformationally locked stereoisomers.B oth conformers followed complex protonation pathwaysinvolving structurally different species,w hich can be targeted under kinetic and thermodynamic control. The neutralization of the ultimate dicationic product, accessible from both stereoisomers of the free base,allowed to realizethe complex conformational switching cycle involving six structurally different species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…10−12 Recently, we have demonstrated that the horizontal expansion of the m-benziporphyrin 13,14 framework could provide the 28-hetero-2,7-naphthiporphyrins 1-X (X = S, Se, Te), which act as macrocyclic ligands for phosphorus-(V). 15,16 The carbaporphyrinoid macrocycles, aside from their role as unusual ligands in coordination and organometallic chemistry, often enable peculiar reactivity within the macrocyclic cavity. 2 Although the core chemistry of N-confused porphyrin, 17,18 the archetypical carbaporphyrinoid, is very well documented, 19 other carbaporphyrinoids are much less studied in this context despite the fact that they were shown to undergo remarkable transformations.…”
mentioning
confidence: 99%
“…10−12 Recently, we have demonstrated that the horizontal expansion of the m-benziporphyrin 13,14 framework could provide the 28-hetero-2,7-naphthiporphyrins 1-X (X = S, Se, Te), which act as macrocyclic ligands for phosphorus-(V). 15,16 The carbaporphyrinoid macrocycles, aside from their role as unusual ligands in coordination and organometallic chemistry, often enable peculiar reactivity within the macrocyclic cavity. 2 Although the core chemistry of N-confused porphyrin, 17,18 the archetypical carbaporphyrinoid, is very well documented, 19 other carbaporphyrinoids are much less studied in this context despite the fact that they were shown to undergo remarkable transformations.…”
mentioning
confidence: 99%